A Robust Method Based on Dual Encoders to Eliminate Velocity Ripple for Modular Drive Joints - Qiang Xin; Chin-Yin Chen; Chongchong Wang; Guilin Yang; Chi Zhang; Zaojun Fang; Chun Lung Philip Chen (Actuators, 2020)
Velocity ripple is one of the common problems of modular drive joints, which easily induces vibration and noise and affects motion accuracy. In order to improve the motion control accuracy, a robust method based on dual encoders to eliminate velocity ripple is proposed in this paper. The method contains a velocity ripple elimination controller (VREC), a rigid-body velocity solver (RBVS), and a proportional–integral (PI) controller. Feeding back the VREC output to the PI controller based on the rigid-body velocity obtained from the weighted sum of dual encoders in the RBVS, an equivalent system damping term was added into the system. Therefore, the velocity ripple can be suppressed effectively with the adjustable damping term composed of control parameters. Above all, the proposed method has only one more parameter to further eliminate velocity ripple compared to the pure PI method and, meanwhile, has apparent advantages over the conventional method, such as fewer parameters and full frequency ripple elimination, as well as robustness to input disturbance and modular drive joint load inertia changes. This proposed method’s effectiveness is verified by simulations in MATLAB and experiments in the modular drive joint platform.